PERAN KELUARGA SEBAGAI LEMBAGA PENDIDIKAN ISLAM PERTAMA - Mirza Syahdat Rambe; Annis Zalwa; Tiara Azmi; Risma Azzahra; Ana Laila (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The family is a fundamental institution from an Islamic perspective, serving as the foundation for a child's personality, faith, and morality before they enter formal education. This study focuses on a comprehensive examination of the family's strategic role as the primary Islamic educational institution and analyzes the challenges of parenting in the digital era. Using a qualitative approach with a library study method, this study examines various scientific literature, books, and academic journals through descriptive-analytical data analysis techniques to synthesize the concept of ideal family education. The study's findings indicate that the successful internalization of Islamic values ​​is highly dependent on parental role models and consistent practice of worship, which effectively shape religious character and children's self-control against the negative influences of modernization. However, the effectiveness of family education is currently hampered by parental time constraints and the massive dominance of digital media. The main conclusion emphasizes that the family is an irreplaceable spiritual fortress that determines the quality of the next generation. Therefore, strengthening the capacity of parents as primary educators is an absolute prerequisite for producing individuals with noble character who are adaptive while remaining steadfast in religious values. The synergy between conceptual understanding and practical role models at home is an essential key to the success of a holistic and sustainable Islamic education. ABSTRAK Keluarga merupakan institusi fundamental dalam perspektif Islam yang berfungsi sebagai peletak dasar kepribadian, akidah, dan moralitas anak sebelum mengenal pendidikan formal. Penelitian ini berfokus untuk mengkaji secara komprehensif peran strategis keluarga sebagai lembaga pendidikan Islam pertama serta menganalisis tantangan pengasuhan di era digital. Menggunakan pendekatan kualitatif dengan metode studi kepustakaan, penelitian ini menelaah berbagai literatur ilmiah, buku, dan jurnal akademik melalui teknik analisis data deskriptif-analitis guna menyintesis konsep pendidikan keluarga yang ideal. Temuan studi menunjukkan bahwa keberhasilan internalisasi nilai keislaman sangat bergantung pada keteladanan orang tua dan konsistensi pembiasaan ibadah yang efektif membentuk karakter religius serta kontrol diri anak terhadap pengaruh negatif modernisasi. Kendati demikian, efektivitas pendidikan keluarga kini terhambat oleh keterbatasan waktu orang tua dan dominasi media digital yang masif. Simpulan utama menegaskan bahwa keluarga adalah benteng spiritual tak tergantikan yang menentukan kualitas generasi penerus, sehingga penguatan kapasitas orang tua sebagai pendidik utama menjadi prasyarat mutlak dalam mencetak individu berakhlak mulia yang adaptif namun tetap teguh pada nilai agama. Sinergi antara pemahaman konseptual dan praktik keteladanan nyata di rumah menjadi kunci esensial keberhasilan pendidikan Islam yang holistik dan berkelanjutan.